Propionate catabolism by CD-associated adherent-invasive E. coli counteracts its anti-inflammatory effect. (1st January 2021) - Agus, Allison; Richard, Damien; Faïs, Tiphanie; Vazeille, Emilie; Chervy, Mélissa; Bonnin, Virginie; Dalmasso, Guillaume; Denizot, Jérémy; Billard, Elisabeth; Bonnet, Richard; Buisson, Anthony; Barnich, Nicolas; et al.
ABSTRACT: Crohn's disease (CD) is a chronic and disabling inflammatory disorder of the gut that is profoundly influenced by intestinal microbiota composition, host genetics and environmental factors. Several groups worldwide have described an imbalance of the gut microbiome composition, called dysbiosis, in CD patients, with an increase in Proteobacteria and Bacteroidetes and a decrease in Firmicutes . A high prevalence of adherent-invasive Escherichia coli (AIEC) pathobionts has been identified in the intestinal mucosa of CD patients. A significant loss in the bacteria that produce short-chain fatty acids (SCFAs) with anti-inflammatory properties, such as propionate, is also a consequence of dysbiosis in CD patients. Here, the AIEC reference strain LF82 was able to degrade propionate in the gut, which was sufficient to counteract the anti-inflammatory effect of propionate both in in vitro models and in mice with DSS-induced colitis. The consumption of propionate by AIEC pathobionts leads to an increase in TNF-α production by macrophages upon infection through the bacterial methyl-citrate pathway. To induce the protective effects of SCFAs on the inflamed gut, we used a G-protein-coupled receptor 43 agonist (GPR43 agonist) that is not metabolizable by intestinal bacteria. Interestingly, this agonist showed anti-inflammatory properties and decreased the severity of colitis in AIEC-infected mice, as assessed by an improvement in the disease activity index (DAI) and a decrease in AIEC pathobiont encroachment. Taken together, these results highlight the effectiveness of GPR43 agonist treatment in the control of gut inflammation and improved our understanding of the ability of AIEC to modulate propionate availability to create an infectious niche to its advantage.